Políticas educacionais da rede pública municipal de ensino de Uberlândia (1997-2004) - Antunes, Marina Ferreira de Souza (2005)
This investigative research had aim to identify and to analyze the politics public educational implemented in the municipal district of Uberlândia, understanding how these politics insert into the globalization and into the reform of the education, which marked the period of time investigated, between the years 1997 to 2004. This research to aim, too, to show what is changing, nowadays, in the municipal public education system, concerns the administration, financial and pedagogical, and to compare the "official discourse" with the political practices which were implemented in reality. For to realize these goals, we used the documental analyze method. The documents researched were: the Organic Law of the municipal district of Uberlândia, and the legal apparatus came from the promulgation, like the laws, the decree, regulations and normative instructions, linked with the municipal education; the law Lei de Diretrizes e Bases LDB 9394/96-; the Parecer 500 of the Minas Gerais State council; and, the journal O Município , which it is the official newspaper of the Uberlândia. In the beginning we did a review about the globalization and how it influence the political education rules. We put focus on the work of multilaterals organisms in this process. Later on we did an analyze the political educational in the municipal district of Uberlândia, based in the facts that emerged the documental research, it means: democratically administration, autonomy, decentralization and participation. After we keep focus on the theoretical reference, that help us to understand how is built one politic public, looking for the educational politics, and after this, we did a comparison between thetheoretical referential and the data updated on the documents researched. At the end we summarize the elements that help us to understand the public educational politics in the municipal district of Uberlândia, looking for the contradictions and putting in focus what was really implemented during the period of time researched.